Faktor-faktor yang Memengaruhi Regulasi Emosi Individu dengan Perilaku Non-Suicidal Self-Injury (NSSI): Tinjauan Literatur - Darapatni, Desak Ayu Shanka Putti; Swandi, Ni Luh Indah Desira (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2024)
This study aims to identify factors that influence emotion regulation in individuals with Non-Suicidal Self-Injury (NSSI) behavior. This study was conducted using the literature review method with a narrative approach by identifying seven quantitative research articles. Non-suicidal self-injury (NSSI) has been associated with the occurrence of decreasing emotion regulation ability. Emotion regulation is an individual's strategy in regulating, feeling, and expressing their emotions. Most studies on NSSI behavior have focused on emotion regulation viewed as an important variable. However, only a few pieces of literature discuss factors influencing emotion regulation in NSSI individuals. This study found that there are two main factors, namely individual and environmental, which influence how NSSI individuals regulate their emotions. Individual factors consist of (1) biological and brain systems; (2) sex and gender; (3) neuroticism; (4) coping self-efficacy; (5) body regard; (6) sleep quality and physical activity, and; (7) borderline personality traits. Furthermore, two environmental factors were found to be influential: (1) social support; and (2) attachment. These findings are expected to provide information to improve the emotion regulation ability in individuals with NSSI behavior.